STRATEGI GURU DALAM MENGEMBANGKAN KECERDASAN LINGUISTIK SISWA - Idi Warsah; Destriani Destriani; Asri Karolina; Riza Faishol (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
The purposes of this study were to describe teacher's strategies in developing students' linguistic intelligence and to find out the supporting and inhibiting factors of teacher's strategies in developing students' linguistic intelligence. This study applied a qualitative approach with data collection techniques that entailed observation, interviews and documentation. The data analysis technique covered data reduction, data presentation, data verification, and drawing a conclusion. The study concluded that the teacher's strategies in developing students' linguistic intelligence rested on the indicators of linguistic intelligence itself. The listening indicator applied the Dictogloss strategy; the reading indicator implemented the Know Want to Learning strategy; the writing indicator used a guided writing strategy; and the speaking indicator deployed a cooperative learning strategy (CLS) by applying a discussion method resulting in that the students were able to explain the materials they had learned well.